PENGARUH PROPORSI OPSI DAN HARGA EKSEKUSI PADA RETURN SAHAM DALAM PELAKSANAAN ESOP DI INDONESIA - Cita Ayu, Putu; Sadha Suardikha, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
This study aims to obtain empirical evidence of the influence of the proportion of stock options and the exercise price on stock retrun in the implementation of the Employee Stock Option Plan (ESOP), which adopts ESOP companies in Indonesia Stock Exchange. Tests carried out using secondary data. Selection of the population is performed using purposive. The results showed that the proportion of stock options proven positive effect on stock returns, the increase the proportion of stock options that were announced, the increase the stock returns enjoyed by shareholders of the company. While the exercise price effect on stock returns at a rate of 10% alpha. Both of these variables are used by investors as a basis for a decision to purchase or dispose of shares of the company Keywords: employee stock option plan, execution price, the proportion option of share, stock returns
Keywords: employee stock option plan, execution price, the proportion option of share, stock returns